The European model of development faced with the quaternary sector emergence test - Dumitru Miron; Dragoș Șeuleanu; Cezar Radu Cojocariu; Laura Benchea (Amfiteatru Economic Journal, 2019)
The European Union must identify and internalize the most acute challenges, prepare appropriate solutions to them, capitalize on its strengths, and avoid threats. The strategic philosophy can no longer be just rhetorical but must be found at the level of all European sectoral policies, national macroeconomic policies but also of the programs and projects launched by the actors operating in the business environment. The research is phenomenological in nature, with an emphasis on qualitative issues related to the most relevant paradigm changes at the level of European sectoral policies, national macroeconomic policies, as well as programs and projects launched by actors operating in the business environment. The topic that plays an important role in this research is the one related to the most appropriate structure of a modern economy, the emphasis being placed on the correlations and the causalities between them. The hypotheses from which it was started, the epistemological perspectives taken as the basis, the analytical drivers used, the research methodologies that were called upon but also the variables used took into account the change of the techno-industrial paradigm, the factors that influence the efficiency and sustainability of the new economic development models, the threats but also the opportunities that must be identified and encountered by those who decide at the macro, mezzo and microeconomic levels. The most important transformations that take place at the level of the macroeconomic and business development models were analyzed, updating them and offering some recommendations on how some systemic vulnerabilities can be treated. The paper ends by surprising the way in which Romania is positioned at the level of the switching process from an economy in which the primary and secondary sectors are prevalent to one in which the weight of the tertiary and quaternary sectors increases.
Keywords: O40; O47; O52; 330; new economic model; paradigm shift; quaternary sector; competitiveness; Romania